Transcription regulation by CHD proteins to control plant development - Hu, Yongfeng; Lai, Yan; Zhu, Deyan (Frontiers in Plant Science, 2014)
CHD (Chromodomain-Helicase-DNA binding) proteins have been characterized in various species as important transcription regulators by their chromatin remodeling activity. However, in plant the function of these proteins has hardly been analyzed before except that Arabidopsis PICKLE and rice CHR729 are identified to play critical roles in the regulation of series of genes involved in developmental or stress responding process. In this review we focus on how plant CHD proteins regulate gene expression and the role of these proteins in controlling plant development and stress response.